CO2 absorption using gas-liquid membrane contactors made of highly porous poly(vinyl chloride) hollow fiber membranes. (September 2016) - Fashandi, Hossein; Ghodsi, Ali; Saghafi, Reza; Zarrebini, Mohammad
Graphical abstract: Highlights: ⿢ Ternary phase diagram of nonsolvent/solvent/polymer system was constructed and considered to rationalize the morphology of highly porous poly(vinyl chloride) (PVC) hollow fiber membranes. ⿢ PVC hollow fiber membranes were developed for the first time for CO2 absorption using gas-liquid membrane contactors. ⿢ The influence of take-up speed on the structure as well as CO2 capture efficiency of produced PVC hollow fibers was investigated and discussed. ⿢ PVC hollow fibers with advantages such as low cost and ease of processability, were introduced as promising candidates for gas-liquid contacting processes. Abstract: Poly(vinyl chloride) (PVC) hollow fiber membranes (HFMs) are considered for the first time to capture carbon dioxide (CO2 ) in a gas-liquid contacting process. To this end, PVC HFMs are produced from PVC/NMP solutions with concentration of 20 wt.% based on liquid⿿liquid phase separation. This is accomplished by changing the take-up speed during spinning process to produce HFMs with different structures. It was found PVC HFMs are promising candidates for CO2 absorption with capacity comparable to that of other hydrophobic polymers such as PVDF, PTFE and PP. In addition, this polymer is more advantageous due to its low cost and good processability. The results also reveal the great contribution of higher flow rate of liquid absorbent, i.e. water, on efficiency of CO2 absorption. Furthermore, the CO2 capture efficiency of PVC HFMs is predominantly determined as a result of trade-off between effects of increasing take-up speed including increased orientation of PVC chains and increased corrugations in the inner contour of HFM along with reduced wall thickness and mean pore size of PVC HFMs. This implies an optimum take-up speed is required to achieve highly effective CO2 capture. Additionally, the influence of water flow rate on efficiency of CO2 absorption becomes more pronounced for HFMs produced under the optimum take-up speed.